Analysis of Breaststroke Technique in Physical Education, Health, and Recreation Students at Karimun University - Fadli Surahman; Hilda Oktri Yeni; Rahmat Sanusi (Universitas Negeri Semarang, 2023)
Observing many students' inadequate ability to effectively and accurately master the breaststroke technique, this study aims to describe the movement analysis in breaststroke technique among Physical Education, Health, and Recreation students at Karimun University. The research focuses on aspects such as body position, arm movement, leg movement, breathing, and coordination. It adopts a quantitative descriptive research design with a population of 30 individuals. The sampling technique used is purposive sampling. Data collection involves direct observation of breaststroke movements by the researcher in the field. After collecting the data, it will be analyzed using quantitative descriptive analysis methods. The research findings are as follows: 1) The ability to master the breaststroke technique can be measured based on the body position indicator, which reaches 62.00%, falling into the